2003
DOI: 10.1242/jcs.00339
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-mediated adhesion is essential for myofibril continuity across the plasma membrane but not for assembly of the contractile apparatus

Abstract: The strong coordinated contraction of heart muscle is dependent on the correct alignment and connection of the myofibrils across the plasma membrane. Previous studies indicate that N-cadherin is involved in cardiac myocyte adhesion and myofibrillogenesis. To investigate whether N-cadherin is specifically required for normal myocyte structure and function, we cultured myocytes from wild-type, N-cadherin-null and mutant embryos expressing the epithelial cadherin E-cadherin. In contrast to previous studies in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 51 publications
3
57
0
1
Order By: Relevance
“…Indeed N-cadherin that associates via catenins to the actin cytoskleton has been described as being involved in myofibrillogenesis, since antibodies blocking N-cadherin function and dissociating cell contacts between myocytes also disrupted myofibril organization (Goncharova et al, 1992;Soler and Knudsen, 1994;Wu et al, 1999). More recently, however, it was found that the overall myofibrillogenesis was normal in N-cadherin deficient cultured cardiomyocytes, whereas the organization of myofibrils and the continuity of the orientation of myofibrils across the plasma membrane to the neighboring cell were disturbed (Luo and Radice, 2003). Interestingly the absence of CAR leads to misalignment of myofibrils across the plasma membrane suggesting that N-cadherin and CAR may both be required for proper myofibril orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed N-cadherin that associates via catenins to the actin cytoskleton has been described as being involved in myofibrillogenesis, since antibodies blocking N-cadherin function and dissociating cell contacts between myocytes also disrupted myofibril organization (Goncharova et al, 1992;Soler and Knudsen, 1994;Wu et al, 1999). More recently, however, it was found that the overall myofibrillogenesis was normal in N-cadherin deficient cultured cardiomyocytes, whereas the organization of myofibrils and the continuity of the orientation of myofibrils across the plasma membrane to the neighboring cell were disturbed (Luo and Radice, 2003). Interestingly the absence of CAR leads to misalignment of myofibrils across the plasma membrane suggesting that N-cadherin and CAR may both be required for proper myofibril orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, tissue culture studies and the analysis of neural crest cell migration in the mouse embryo have shown that the assembly and function of gap junctions is directly controlled by Eand N-cadherins, respectively (Jongen et al 1991;Musil et al 1990;Fujimoto et al 1997;Xu et al 2001). Inhibition of cadherin function, such as in N-cadherin-deficient myocytes, can disrupt gap junction formation and inhibit cell-cell coupling, suggesting that localization of cadherin to cell-cell contact sites may be a prerequisite for gap junction formation (Meyer et al 1992;Luo and Radice 2003). Conversely, inhibition of connexin43 can block adherens junction formation (Zuppinger et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…35 Furthermore in our studies, cell surface expression of Cx43 is restored in N-cadherin-null embryonic cardiomyocytes after introduction of a cadherin transgene. 36 Another study showed that immunohistochemical analysis of dissociated adult rat ventricular myocytes reveals that the expected levels of N-cadherin, β-catenin and plakoglobin are present with only a small amount of connexin at early stages of culture (days 3 to 4). Gap junctions became evident only once complete adherens junctions had formed and in all cases the new gap junctions were immediately adjacent to the adherens junctions (culture days 6 to 12).…”
Section: Altered Gap Junction Function In the Pathogenesis Of Cardiacmentioning
confidence: 99%